A quality control study on RBA Engineering Company - Aquino, Ryan Jose T. (College of Engineering, 2000)
RBA Engineering and Machine Shop was established in 1984 and is engaged in car parts manufacturing, metal fabrication, fabrication of jigs and fixtures and engineering services. The clients of RBA are usually large companies who have opted to sub-contract the parts they need. The company started with only four machines and four employees in a rented lot. Today, RBA has its own lot, many additional machines and 19 employees. Using different techniques in Quality Control analysis, the group has documented the quality of the shim, the product which is produced in greatest volume. Using Failure Mode Effects and Analysis, Ishikawa Diagrams and Pareto Charts, the group has determined the three major problem areas of the shim. The first problem with the manufacture of the shim is the development of sharp edges during the blanking process. The second problem is the varying distance of the holes center from the edges. The third problem is the manifestation of scratches on the products thereby resulting in poor appearance. By taking samples from the production lines, the group was able to develop control charts for the three problem areas. Then by using stability analysis and then capability analysis, the processes were fixed and then found as feasible. The group also applied quality cost analysis for the failures and problems involved in the non-conformities of the product as well as the treatment and prevention of the non-conformities. The group then generated alternatives which were aimed at dealing with the problem areas. By evaluating the alternatives afterwards, the group was able to give recommendations and steps on how they could be implemented.